Analisis Keaktifan Kolaborasi Guru IPA Menggunakan Aplikasi Google Docs di Masa Pandemi Covid-19 - Merlanita Firsty Mariadini; Muhammad Fauzi Nurromadhon; Ria Anisa Fani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2021)
Covid-19 as a global pandemic has an impact on accelerating technological transformation. Teachers are expected to master technological advances to become innovative, creative, and able to work together, one of which is in learning science. This study was conducted to analyze the collaborative activities of science teachers using the google docs application during the Covid-19 pandemic. The method used in this research is descriptive with a qualitative approach. The research subjects were science teachers, totaling 90 people. The data collection technique used is observation and field notes. The research was conducted online using Google docs, Zoom, and Whatsapp. Technical analysis of the data using the Miles & Huberman model consists of data reduction, data display, and verification. The results showed that 83.3% of collaborations were very good, while the remaining 16.7% were considered good collaborations. The result is because the collaboration participants are enthusiastic and interested in participating in the collaboration. It is shown by the participants' active participation and participation in questions and answers during the discussion. However, the collaboration of science teachers was not fully achieved following the indicators of collaboration activity due to obstacles during the implementation of collaboration, such as unstable internet networks, inadequate gadgets, and limited LKPP processing time.